The Use of Zirconia Implants in Patients with Metal Allergies - Dhafer hassan Alshehri,; Riyadh mohammed albadr,; Saleemah saleh albogmy,; Majed Aydh alotaibi,; Abdulbari Mohammed Aleidan,; Tawfik Shami Alayafi,; Kholoud abdullah alnemer,; Abdulaziz Fahad AlShalhoub,; Ali Mohammed Alfareh,; Rakan Nejer Alotaibi,; Nouf Ibrahim Almkezem, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The advent of zirconia implants has garnered significant interest in implant dentistry, particularly for patients with metal allergies or hypersensitivity reactions to traditional titanium implants. This paper provides a comprehensive review of the clinical outcomes of zirconia implants and their potential application in patients with documented metal allergies. Drawing from a recent systematic review and meta-analysis, the paper discusses osseointegration, survival rates, marginal bone loss, and implant fracture rates associated with zirconia implants. The estimated 10-year cumulative survival rate was 95.1%, with marginal bone loss values comparable to titanium implants. However, limitations in available data, including short follow-up periods and confounding factors, are acknowledged. The paper explores the potential advantages of zirconia implants, such as hypoallergenic properties, reduced risk of adverse reactions, and improved aesthetics. Conversely, limitations like limited long-term data, implant fractures, osseointegration concerns, cost and availability, and surgical and restorative considerations are discussed. Clinical recommendations emphasize comprehensive patient selection, allergy testing, case assessment, treatment planning, adherence to protocols, patient education, and long-term monitoring. Furthermore, future directions and research needs are highlighted, including large-scale, long-term studies, implant design and surface modifications, investigations into bone-implant interface and aging effects, exploration of patient-specific factors and personalized approaches, comparative studies with titanium implants, and interdisciplinary collaboration. While promising, the use of zirconia implants in metal allergy patients requires a cautious, evidence-based approach considering patient-specific factors, clinician expertise, and evolving scientific knowledge.